2019
DOI: 10.1371/journal.pone.0220002
|View full text |Cite
|
Sign up to set email alerts
|

Home care aides’ observations and machine learning algorithms for the prediction of visits to emergency departments by older community-dwelling individuals receiving home care assistance: A proof of concept study

Abstract: Background Older individuals receiving home assistance are at high risk for emergency visits and unplanned hospitalization. Anticipating their health difficulties could prevent these events. This study investigated the effectiveness of an at-home monitoring method using social workers’ observations to predict risk for 7- and 14-day emergency department (ED) visits. Methods This was a prospective cohort study of persons ≥75 years, living at home and receiving assistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Third, working conditions can be poor and isolating [16,17]. Despite this, studies have shown that HCWs generally like their jobs, find them meaningful, and can have a positive impact on patient outcomes, when utilized at their skill level [18,19]. Our findings also demonstrate how the principles of implementation science could be used to leverage technology and advance the role of HCWs in the context of HF care.…”
Section: Discussionmentioning
confidence: 76%
“…Third, working conditions can be poor and isolating [16,17]. Despite this, studies have shown that HCWs generally like their jobs, find them meaningful, and can have a positive impact on patient outcomes, when utilized at their skill level [18,19]. Our findings also demonstrate how the principles of implementation science could be used to leverage technology and advance the role of HCWs in the context of HF care.…”
Section: Discussionmentioning
confidence: 76%
“…Even though it is still a novel area of research, prediction models developed to predict the risk of acute hospitalization among older community-dwelling citizens have been found to be effective in achieving predictive performance [ 18 20 ]. These models have primarily been developed based on health care data from electronic hospital records.…”
Section: Discussionmentioning
confidence: 99%
“…Most models are based on data from electronic hospital records and many have been found effective in predicting risk of acute admissions [ 13 – 19 ]. Only a few studies have focused on prediction models solely based on home care data [ 20 ], and very few studies have implemented and tested a prediction model in practice, mainly due to ethical and economic considerations [ 21 ], barriers among professionals, such as trust in the technology [ 22 ], and the fact that data on health and care is registered primarily for the use and support for health professionals, not for input to algorithms [ 23 ]. Thus, datasets are more often designed for retrospective analysis than for prospective use [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient (or family)-reported outcome measure (PROM) systems benefit patients with chronic diseases by improving quality of life, reducing mortality, reducing ED visits, and hospitalizations [12][13][14]. In 2019, we conducted an observational cohort study, enrolling 301 older individuals who received regular visits by home aides (HAs); we developed a machine learning algorithm to predict the risk of emergency visits, with a prediction window of 7-14 days and a predictive performance (ie, the area under the receiver operating characteristic curve) of 0.70 after 7 days and 0.67 after 14 days [15]. This algorithm opens the possibility of mobilizing health professionals to intervene early in an acute illness or in the decompensation of a chronic illness before they lead to an ED visit and unplanned hospitalization.…”
Section: Introductionmentioning
confidence: 99%